2008
DOI: 10.1007/s00792-008-0210-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and archaeal populations at two shallow hydrothermal vents off Panarea Island (Eolian Islands, Italy)

Abstract: The aim of this study was to investigate the microbial community thriving at two shallow hydrothermal vents off Panarea Island (Italy). Physico-chemical characteristics of thermal waters were examined in order to establish the effect of the vents on biodiversity of both Bacteria and Archaea. Water and adjacent sediment samples were collected at different times from two vents, characterised by different depth and temperature, and analysed to evaluate total microbial abundances, sulphur-oxidising and thermophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 55 publications
5
56
1
1
Order By: Relevance
“…Branching of the environmental sequences almost exclusively between unculturable Archaea has been already observed not only for hot springs [6,31] but also for other places where Archaea diversity was studied [32]. Most of the sequences retrieved in this study were related to Crenarchaeota, unlike the results from Panarea Iceland, where euryarchaeotic diversity in hydrothermal vents was significantly higher [33]. Almost quarter of the sequences belonged to the group of HSS.…”
Section: Clustering Of Varvara Sequences Predominantly Between Envirocontrasting
confidence: 57%
See 1 more Smart Citation
“…Branching of the environmental sequences almost exclusively between unculturable Archaea has been already observed not only for hot springs [6,31] but also for other places where Archaea diversity was studied [32]. Most of the sequences retrieved in this study were related to Crenarchaeota, unlike the results from Panarea Iceland, where euryarchaeotic diversity in hydrothermal vents was significantly higher [33]. Almost quarter of the sequences belonged to the group of HSS.…”
Section: Clustering Of Varvara Sequences Predominantly Between Envirocontrasting
confidence: 57%
“…Lack of specificity was observed in other investigations. Maugeri et al [33] reported the identification of 16S rRNA gene sequences affiliated to uncultured clones of Archaea from hot springs and hydrothermal vents of different geographical zones. Correspondingly newly described culturable Archaea were grouped together with already described culturable 16S rRNA genes [36].…”
Section: Clustering Of Varvara Sequences Predominantly Between Enviromentioning
confidence: 99%
“…1b). In both areas, emissions are marked by white deposits of colloidal sulfur associated with microbial activity (Gugliandolo et al, 1999;Italiano and Nuccio, 1991;Maugeri et al, 2009). …”
Section: Hydrothermal Activity and Samplingmentioning
confidence: 99%
“…Metagenome analysis supports the relevance of sulfur metabolism and of the rTCA cycle for autotropic life at Hot Lake (Huang, 2012). Maugeri et al (2009), suggested that sulfur-oxidizing bacteria were detected by both culture-dependent and -independent methods at two nearby sites within the Panarea submerged caldera.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…DGGE of PCR amplified 16S rDNA fragments have been used to profile community complexity of microbial mats and bacterial biofilms of a wide variety of ecosystems. DGGE analysis of PCR amplified rDNA fragments has been used to provide information on the microbial diversity of microbial communities associated to hydrothermal vents (Li et al, 2008;Maugeri et al, 2009), soil (Vaario et al, 2011) or extreme acidic environments (González-Toril et al, 2003) (Fig.1). PCR-DGGE has been applied to profile the distribution of microbial populations inhabiting regions with different temperatures in hot spring cyanobacterial communities (Aditiawati et al, 2009;Teske et al, 2009), to identify bacteria in a biodegraded wall painting (Rolleke et al, 1996) or historical limestone buildings (Ettenauer et al, 2011).…”
Section: Denaturing Gradient Gel Electrophoresis (Dgge)mentioning
confidence: 99%